One Year Health Status Benefits Following Treatment for New Onset or Exacerbation of Peripheral Arterial Disease Symptoms: The Importance of Patients' Baseline Health Status. Issue 2 (August 2015) - van Zitteren, M.; Denollet, J.; Heyligers, J.M.; Elshof, J.W.M.; Nooren, M.J.; Burger, D.H.; de Fijter, W.M.; Vriens, P.W.; Smolderen, K.G.
Abstract : Objective/Background: Limited information is available on expected health status gains following invasive treatment in peripheral arterial disease (PAD). One year health status outcomes following invasive treatment for PAD were compared, and whether pre-procedural health status was indicative of 1 year health status gains was evaluated. Methods: Pre-procedural and 1 year health status (Short Form-12, Physical Component Score [PCS]) was prospectively assessed in a cohort of 474 patients, enrolled from 2 Dutch vascular clinics (March 2006–August 2011), with new or exacerbation of PAD symptoms. One year treatment strategy (invasive vs. non-invasive) and clinical information was abstracted. Quartiles of baseline health status scores and mean 1 year health status change scores were compared by invasive treatment for PAD. The numbers needed to treat (NNT) to obtain clinically relevant changes in 1 year health status were calculated. A propensity weight adjusted linear regression analysis was constructed to predict 1 year PCS scores. Results: Invasive treatment was performed in 39% of patients. Patients with baseline health status scores in the lowest quartile undergoing invasive treatment had the greatest improvement (mean invasive 11.3 ± 10.3 vs. mean non-invasive 5.3 ± 8.5 [ p = .001, NNT = 3]), whereas those in the highest quartile improved less (.8 ± 6.3 vs. –3.0 ± 8.2 [ p = .025, NNT = 90]). Undergoing invasive treatment ( p < .0001) and lower baseline health status scores ( p < .0001) were independently associated with greater 1 year health status gains. Conclusion: Substantial improvements were found in patients presenting with lower pre-procedural health status scores, whereas patients with higher starting health status levels had less to gain by an invasive strategy.